The growth of computer-assisted (robotic) surgery in urology 2000–2014: The role of Asian surgeons - Deepansh Dalela; Rajesh Ahlawat; Akshay Sood; Wooju Jeong; Mahendra Bhandari; Mani Menon (Asian Journal of Urology)
Objective: A major role in the establishment of computer-assisted robotic surgery (CARS) can be traced to the work of Mani Menon at Vattikuti Urology Institute (VUI), and of many surgeons of Asian origin. The success of robotic surgery in urology has spurred its acceptance in other surgical disciplines, improving patient comfort and disease outcomes and helping the industrial growth. The present paper gives an overview of the progress and development of robotic surgery, especially in the field of Urology; and to underscore some of the seminal work done by the VUI and Asian surgeons in the development of robotic surgery in urology in the US and around the world. Methods: PubMed/Medline and Scopus databases were searched for publications from 2000 through June 2014, using algorithms based on keywords “robotic surgery”, ”prostate”, “kidney”, “adrenal”, “bladder”, “reconstruction”, and “kidney transplant”. Inclusion criteria used were published full articles, book chapters, clinical trials, prospective and retrospective series, and systematic reviews/meta-analyses written in English language. Studies from Asian institutions or with the first/senior author of Asian origin were included for discussion, and focused on techniques of robotic surgery, relevant patient outcomes and associated demographic trends. Results: A total of 58 articles selected for final review highlight the important strides made by robots in urology, from robotic radical prostatectomy in 2000 to robotic kidney transplant in 2014. In the hands of an experienced robotic surgeon, it has been demonstrated to improve functional patient outcomes and minimize perioperative complications compared to open surgery, especially in urologic oncology and reconstructive urology. With increasing surgeon proficiency, the benefits of robotic surgery were consistently seen across different surgical disciplines, patient populations, and strata. Conclusion: The addition of robot to the surgical armamentarium has allowed better patient care and improved disease outcomes. VUI and surgeons of Asian origin have played a pioneering role in dissemination of computer-assisted surgery.